Implementing ACOVE Quality Indicators as an Intervention Checklist to Improve Care for Hospitalized Older Adults. Issue 7 (1st July 2017) - Sinvani, Liron; Kozikowski, Andrzej; Smilios, Christopher; Patel, Vidhi; Qiu, Guang; Akerman, Meredith; Lesser, Martin; Rosenberg, David; Wolf‐Klein, Gisele; Pekmezaris, Renee
Abstract : BACKGROUND: Medicare patients account for approximately 50% of hospital days. Hospitalization in older adults often results in poor outcomes. OBJECTIVE: To test the feasibility and impact of using Assessing Care of Vulnerable Elders (ACOVE) quality indicators (QIs) as a therapeutic intervention to improve care of hospitalized older adults. DESIGN: Post‐test only prospective intervention with a non‐equivalent retrospective control group. SETTING: Large tertiary hospital in the greater New York Metropolitan area. PATIENTS: Hospitalized patients, 75 years and over, admitted to medical units. INTERVENTION: A checklist, comprised of four ACOVE QIs, administered during daily interdisciplinary rounds: venous thrombosis prophylaxis (VTE) (QI 1), indwelling bladder catheters (QI 2), mobilization (QI 3), and delirium evaluation (QI 4). MEASUREMENTS: Variables were extracted from electronic medical records with QI compliance as primary outcome, and length of stay (LOS), discharge disposition, and read‐missions as secondary outcomes. Generalized linear mixed models for binary clustered data were used to estimate compliance rates for each group (intervention group or control group) in the postintervention period, along with their corresponding 95% confidence intervals. RESULTS: Of the 2, 396 patients, 530 were on an intervention unit. In those patients not already compliant with VTE, compliance rate was 57% in intervention vs 39% in control ( P < .0056). For indwelling catheters, mobilization, and delirium evaluation, overall compliance was significantly higher in the intervention group 72.2% vs 54.4% ( P = .1061), 62.9% vs 48.2% ( P < .0001), and 27.9% vs 21.7% ( P = .0027), respectively. CONCLUSION: The study demonstrates the feasibility and effectiveness of integrating ACOVE QIs to improve the quality of care in hospitalized older adults.